A disseminação do ideário pedagógico capitalista na educação do campo no estado de Goiás: o Programa Agrinho na escola (2008-2020) - Alves, Jackeline Silva (Universidade Federal de São Carlos, 2021)
In Brazil, historically, the education offered to the populations that live and work in the countryside, has been the object of contradictions and it is possible to determine “gaps” that merges with such offer. The children’sschcooling process of the working class in the countryside and in the city, often were committed to the preparation of the workforce necessary for the dynamization of the productive processes. Since the Federal Constitution of 1988, the set of Brazilian norms that govern Educational Policy in the country, opened possibilities for public-private partnerships in Education, and in this sense Educational Programs managed by companies, institutions and foundations materialize in the school space public. Since the Federal Constitution of 1988, the set of Brazilian norms that govern Educational Policy in the country, opened possibilities for public-private partnerships in Education, and in this sense Educational Programs managed by companies, institutions and foundations materialize in the school space public. In view of this, the objective of this research is to identify and understand the contradictions that permeate the Agrinho Social Responsibility Program, in the offer of education in the countryside in Goiás. Aiming to achieve this intent, we defined as specific objectives: to know and identify: the pedagogical and methodological conceptions that underlie the Program; to verify the educational practices guided by this; to analyze the relativization of the teacher's role in mediating the knowledge construction process by the student; as well as on the role of this Program in the elaboration of school knowledge accessed by working class children from the countryside and the city, considering that the concepts and strategies used for the construction of knowledge in the perspective defended by the aforementioned Program are in line with the interests of capital reproduction , by spreading and reinforcing the importance of agribusiness as a productive and viable development model for the entire Brazilian countryside. In order to achieve the proposed objective, we followed the following methodological path: survey and review of theoretical sources that deal with the topic together with books, theses, dissertations and scientific articles; documentary research with the Laws, Norms, Decrees and Resolutions that deal with the education offered in the field, about the possibilities of public-private partnerships in education; and guidelines for Rural Education; conducting the Training Course for Educational Agents for the Agrinho Program in a Virtual Learning Environment; survey of data and information about the Program with the National Rural Apprenticeship Service (SENAR) and the Federation of Agriculture and Livestock of the State of Goiás. The results achieved reveal contradictions and conflicts of interest between what is proposed by the Program and the desires of an education project in the field that is socially referenced and that fosters the development of critical thinking that allows the understanding of multiple contradictions and different realities that make up the totality of the Brazilian field. Agrinho is a Program that has a strong relationship with rural employers, with companies linked to the development of agribusiness, and with investing institutions. Therefore, as agribusiness is a productive model that is highly dependent on the use of pesticides and causes the degradation of the environment, we do not see interest in shed light on the contradictions that arise from the relationship between agricultural production/use of pesticides for human health and for the environment.
The dissemination of capitalist pedagogical ideas in rural education in the state of Goiás: the Agrinho Social Program in the school (2008-2020)
Keywords: Educação no campo; Programas educacionais; Responsabilidade social; Público-privada; Agrinho; Rural education; Educational programs; Social responsability; Public-private partnerships; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO